Bullets No More - Shaka, Jack (Moving Framez Africa, 2008)
Verzio FF Submission The film analyzes the post-election violence that rocked Kenya in 2007 – 2008. It brings into focus the carnage that followed the elections – the plight of the refugees and the suffering of the internally displaced people. It takes the viewer on an extensive journey, following closely the events as they began, unfolded and finally ended with the results of the election being released and the Peace Accord being signed.